Climate change adaptation in the management of public buildings: an Indonesian context. Issue 2 (8th April 2019) - Lukito, Jose Arif; Susilawati, Connie; Goonetilleke, Ashantha
Abstract : Purpose: The purpose of this paper is to provide a strategy to integrate climate change adaptation (CCA) in public asset management (PAM) in Indonesia. This paper focusses on public buildings as part of a public asset. Design/methodology/approach: As an archipelagic country, Indonesia is very vulnerable to sea-level rise as a result of climate change. The outcomes of a qualitative analysis of interviews with relevant stakeholders were used for the development of the CCA framework in an Indonesian context. Findings: The study identified that the integration of CCA in PAM in Indonesia requires the incorporation of nine key elements. These are as follows: recognition of climate change; risk management and insurance schemes for assets; integrated asset management and planning; asset use and knowledge; reliable, accessible and understandable data set on climate change; leadership, government commitment and incentives; involvement of research and private entities; community engagement; and coordination of relevant agencies. Research limitations/implications: This paper informed only the key elements required on the development of framework which integrate CCA in PAM. Practical implications: The integration of CCA to a PAM framework will support the development of policies and procedures for better-informed decisions. Social implications: The framework increases opportunities for stakeholders and community engagement in policy development and decision making in relation to CCA for public assets. Originality/value: This paper synthesises CCA and PAM using knowledge from the three levels of governments in Australia and Indonesia. CCA and PAM groups work separately in Indonesia and integration will reduce climate change risks and improve decision making in PAM.